Prácticas de laboratorio para mejorar el aprendizaje de movimiento de los cuerpos en una dimensión, en el primer año de bachillerato general unificado de la unidad educativa anexa a la UNL de la ciudad de Loja, periodo 2013-2014 - Labanda Alban, Jorge Luis (2015)
The research objective was to consider the practices of laboratory to improve the learning of movement of the bodies in a DIMENSION, in the first year of high school GENERAL unified of the unit educational APPENDED to the UNL, from the city of LOJA, 2013-2014 period. The object of the research process consisted of used laboratory practices to improve the learning of movement of bodies in a dimension. Research responded to a descriptive design (diagnosis) and experimental pre. Phases followed in your order were as follows: comprehensive that allowed us to accept and understand the cause; the diagnosis was performed on the database and facts collected and ordered systematically allowing you to better judge what is happening; models which will allow to demonstrate the alternative that arises; application which allows you to check the proposed alternative; and for the evaluation of the effectiveness which admits to check if the alternative allows to improve the learning of movement of bodies in a dimension. The difficulties, shortcomings or cognitive needs present in the learning of movement of bodies in a dimension can be minimised or mitigate the application of laboratory practice.